A comparative study on the incidence of Entamoeba histolytica and Entamoeba coli in man. - Corneja, Anna Lyn C.
A study was conducted to determine the incidence of amoebiasis (Entamoeba histolytica and E. Coli) in patients examined at the West Visayas State University Hospital and Representative Pedro G. Trono Memorial Hospital, and establish a baseline information on amoebic infestation. This study made use of 3,555 patients examined from the rural area and 2,889 patients examined in the urban area in the year 1992. In addition to this, fecal samples of 100 patients were actually examined in each of the two hospitals in April 1994 and was used as a subsample. Amoebic infection was recorded and classified according to the human host's age, sex, locality (urban or rural), and species of amoeba involved., The results indicated that Entamoeba histolytica infection occur highest in age range 56 - 69, while E. coli infection occur highest in 84 - 97 age range. Statistical analysis of the results indicated that amoebic infection may occur in various age ranges. This depends on the prevailing levels of personal and environmental hygiene practiced by an indvidual. Male hosts were found to be more susceptible to E. histolytica than female hosts. On the other hand, e. coli infection was equal in both sexes. Amoebic infection was significantly higher in the rrural residents comapred to that in the urban residents, this may be due to the dependence of rural inhabitants to untreated wells, springs and streams for drinking water which may be contaminated by local sewage. The number of infections caused by E. histolytica was also signifcantly higher than that caused by E. coli, this may be attributed to its higher capacity to invade the host which may be due to its higher pathogenic activity and virulence.